A Wonderful Linkage of Beings: Hierarchy and the Cultural Instruments of Social Organization in Elizabethan England - McCracken, Grant (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1988)
The social hierarchy of Elizabethan England was stoutly and exactly "hinged". At every point ranks touched in the hierarchy, cultural instruments worked to establish a connection between them. The purpose of the present paper is to give an anthropological account of two of these cultural instruments, showing how they served the concept and the practice of Elizabethan social organization. The cultural instruments in question are courtesy and child exchange.